Answer:
b. 36
Explanation:
Evaluate x^4 - 4 x^2 + 3 x where x = -3:
x^4 - 4 x^2 + 3 x = (-3)^4 - 4×(-3)^2 - 3×3
Hint: | Evaluate (-3)^2.
(-3)^2 = 9:
(-3)^4 - 49 - 3×3
Hint: | Determine the sign of (-3)^4.
(-3)^4 = (-1)^4×3^4 = 1×3^4:
3^4 - 4×9 - 3×3
Hint: | Compute 3^4 by repeated squaring.
3^4 = (3^2)^2:
(3^2)^2 - 4×9 - 3×3
Hint: | Evaluate 3^2.
3^2 = 9:
9^2 - 4×9 - 3×3
Hint: | Evaluate 9^2.
9^2 = 81:
81 - 4×9 - 3×3
Hint: | Multiply -4 and 9 together.
-4×9 = -36:
81 + -36 - 3×3
Hint: | Multiply 3 and -3 together.
3 (-3) = -9:
81 - 36 + -9
Hint: | Group the negative terms in 81 - 36 - 9 together and factor out the minus sign.
81 - 36 - 9 = 81 - (36 + 9):
81 - (36 + 9)
Hint: | Evaluate 36 + 9 using long addition.
| 1 |
| 3 | 6
+ | | 9
| 4 | 5:
81 - 45
Hint: | Subtract 45 from 81.
| 7 | 11
| 8 | 1
- | 4 | 5
| 3 | 6:
Answer: 36